1981
DOI: 10.1177/014662168100500307
|View full text |Cite
|
Sign up to set email alerts
|

Analogical Reasoning Under Different Methods of Test Administration

Abstract: One hundred eighty-five college undergraduates were given the Advanced Progressive Matrices un der one of five conditions of testing: standard, simple feedback, examinee verbalization during problem solution, elaborated feedback, and full elaboration. The Group Embedded Figures Test, Paragraph Completion Test, and Zelniker and Jeff rey's revision of the Matching Familiar Figures Test were also administered. The study was designed (1) to investigate the differential effects of method of test administration on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…But there is also evidence that low scoring subjects sometimes use very different processes on the Raven test, which could obscure the relationship between Raven test performance and working memory for such individuals. For example, as mentioned previously, low-scoring subjects rely more on a strategy of eliminating some of the response alternatives, fixating the alternatives much sooner than high-scoring subjects (Bethell-Fox et al, 1984; Dillon & Stevenson-Hicks, 1981). Moreover, the types of errors made by low-scoring adults frequently differ from those made by high-scoring subjects (Forbes, 1964) and may reflect less analysis of the problem.…”
Section: Comparing Human Performance To the Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…But there is also evidence that low scoring subjects sometimes use very different processes on the Raven test, which could obscure the relationship between Raven test performance and working memory for such individuals. For example, as mentioned previously, low-scoring subjects rely more on a strategy of eliminating some of the response alternatives, fixating the alternatives much sooner than high-scoring subjects (Bethell-Fox et al, 1984; Dillon & Stevenson-Hicks, 1981). Moreover, the types of errors made by low-scoring adults frequently differ from those made by high-scoring subjects (Forbes, 1964) and may reflect less analysis of the problem.…”
Section: Comparing Human Performance To the Theorymentioning
confidence: 99%
“…The lower scoring subjects sometimes scanned the response alternatives before inducing the rules, particularly in the case of the more difficult problems. Other researchers have also found that lower scoring subjects are more likely to use response-elimination strategies for geometric analogy problems, whereas higher scoring subjects are more likely to determine the properties of the desired response before examining the response alternatives (Bethell-Fox, Lohman, & Snow, 1984; Dillon & Stevenson-Hicks, 1981).…”
Section: The Simulation Modelsmentioning
confidence: 99%
“…When constraining the focus on accuracy feedback the result pattern homogenises to small and zero performance effects (Carlson & Wiedl, 1979;Dash & Rath, 1984;Dillon, 1981;Kluger & DeNisi, 1996). This indicates that the level of elaborateness of feedback acts as a situation-related moderator variable.…”
mentioning
confidence: 99%
“…The researchers found clinically and statistically significant differences in test scores when the story was presented at the slow speed versus the other speeds. More explicit instructions and verbalization during problem solving seem to correlate with improved performance on measures such as WAIS Digit Symbol and Wisconsin Card Sorting Test (Dillon, 1981;Joncas & Standing, 1998;Perry, Potterat, & Braff, 2001). Therefore, across various neuropsychological tests, deviations in standard administration can have a significant affect on test scores.…”
Section: Introductionmentioning
confidence: 99%